2004
DOI: 10.1515/bc.2004.032
|View full text |Cite
|
Sign up to set email alerts
|

The periplasmic E. coli chaperone Skp is a trimer in solution: biophysical and preliminary crystallographic characterization

Abstract: The 'seventeen kilodalton protein' Skp confers transient solubility on outer membrane proteins during biogenesis in Gram-negative bacteria. Here we report a first biophysical characterization of this chaperone itself, which also possesses biotechnological potential in the production of recombinant proteins. Using cross-linking and gel filtration methods, we found that Skp forms a stable homo-trimer in solution. Following thermal denaturation, monitored by CD spectroscopy, this chaperone refolds with high effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…10 Pulse labeling and biochemical reconstitution experiments suggested that LPS may be required for efficient assembly of OMPs such as trimeric PhoE, 16 and monomeric OmpA, 17 into outer membranes. Skp consists of 141 amino acid residues and forms a stable homotrimer, 18 consistent with the previously determined stoichiometry of Skp in complex with unfolded OmpA. 12 The trimer resembles a jellyfish and is formed of a tentacle domain with α-helical tentacles that protrude about 60 Å from a β-barrel body termed the association domain.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…10 Pulse labeling and biochemical reconstitution experiments suggested that LPS may be required for efficient assembly of OMPs such as trimeric PhoE, 16 and monomeric OmpA, 17 into outer membranes. Skp consists of 141 amino acid residues and forms a stable homotrimer, 18 consistent with the previously determined stoichiometry of Skp in complex with unfolded OmpA. 12 The trimer resembles a jellyfish and is formed of a tentacle domain with α-helical tentacles that protrude about 60 Å from a β-barrel body termed the association domain.…”
Section: Introductionsupporting
confidence: 83%
“…18 However, the binding stoichiometry may depend on the size of the OMP or its transmembrane domain. To obtain stoichiometries and to estimate the strength of Skp binding, we recorded fluorescence spectra of the aqueous forms of each OMP after dilution of the urea as a function of the molar Skp/OMP ratio until no further increase of the fluorescence intensity was observed ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The Skp structure was unexpectedly similar to that of prefoldin, a cytosolic molecular chaperone present in archea and eukarya (8)(9)(10). Although Skp is a trimer (8,9,11) and prefoldin is a hexamer (12,13), both proteins share jellyfish architectures with a central cavity ( Fig. 1 A and B).…”
mentioning
confidence: 85%
“…As previously mentioned, Skp is a homotrimeric periplasmic chaperone for newly synthesized OMPs. [15][16][17][18] Three hairpin-shaped α-helical extensions extend ~60 Å from the trimerization domain, which is composed of 3 intersubunit β-sheets that wind around a central axis. From observations of its secondary structure, the amino acid sequences of the Omp1-like protein from A. actinomycetemcomitans were not well matched with those of the Skp from E. coli, but both sets were composed mostly of α-helices.…”
Section: Resultsmentioning
confidence: 99%